Pengaruh Ekstrak Bintaro (Carbera odollam Gaertn) dan Kecubung (Brugmansia candida Pers) terhadap Rayap Tanah Coptotermes sp Influence of Bintaro (Carbera odollam Gaertn) and Kecubung (Brugmansia candida Pers) Extract against Subterranean Termite Coptotermes sp - Didi Tarmadi; Arief H Prianto; Ikhsan Guswenrivo; Titik Kartika; Sulaeman Yusuf (Masyarakat Peneliti Kayu Indonesia, 2007)
Subterranean termite especially Coptotermes sp has been spread widely and has caused a tremendous economical loss. Various chemical compounds have been used to overcome termite attack. However, utilization of chemical could endanger the environment, thus it is important to find another compound which can be used as an environmental friendly wood preservatives. One of the alternatives is to extract natural compound which has an anti-insect peculiarity. Fruits, leaves and barks of Bintaro and Kecubung, especially their leaves and flowers have been widely known as traditional medicine. This paper explains the effects of the extracts of Bintaro (leaves and bark) and Kecubung (leaves) on subterranean termite of Coptotermes sp.Leaves and bark powder of Bintaro and leaves powder of Kecubung were extracted with n-hexane, ethyl acetate, acetone, and methanol. Paper disc which has been dropped by the extract solution was used as bait to subterranean termite of Coptotermes sp. The observation of termite mortality was calculated for every two days during 10 days of observation. The result shows that Bintaro leaves extracted with methanol caused 100% termite mortality on last observation. Whereas on Bintaro bark extracted with n-hexane and acetone caused 100% termite mortality on eighth day of the treatment. Kecubung leaves extracted with n-hexane and ethyl acetate caused 100% termite mortality on last observation